An Automated Feeding System for Soft Shell Crab - Muhammad Niswar; Zahir Zainuddin; Yushinta Fujaya; Zagita Marna Putra (Institute of Advanced Engineering and Science, 2017)
Soft shell crab farming has been practiced in south-east Asian countries such as Indonesia. Soft shell crabs are harvested when they have just molted to prevent their shells from being hardened. An issue arises when feeding the crabs. Farmers need to feed the crabs 5% food of their body weight. However, farmers sometimes provide incorrect amounts of food to the crabs. If farmers feed the crab exceeding the required amounts of food, it causes food wastage and dirty water in the crabs’ cage. On the other hand, less amounts of food causes slow growth and molting of the crabs. In this study, we developed an automated feeding system for properly feeding of soft-shell crabs. The automated feeding system schedules the feeding time and controls the portion of food using a microcontroller. We also developed a web-based monitoring system to monitor and generate alert message to farmers to make sure that feeding process runs properly.